DESIGN AND BUILD OF 1 (ONE) AXIS PLASMA CUTTING MECHANISM - I Wayan Suma Wibawa (Logic : Jurnal Rancang Bangun dan Teknologi, 2022)
Plasma cutting is a cutting process that is widely used by the metal industry and individuals. Plasma cutting is widely used because it has many advantages, including: Cheap tools and widely sold in the market, low operating costs because they use electric power and compressed air from a compressor, unlike oxyacetylene cutting which requires oxygen, the available tools are more flexible and easy moved. The use of plasma cutting is relatively easy, by setting the machine and then directing the plasma torch to the cutting plane as needed by maintaining a stable movement and height. However, when we are going to make repeated cuts, our concentration and physical power will automatically decrease, so we need a tool that can assist us in directing/regulating the plasma in which the tool functions as a plasma cutting mechanism. Based on this background, the author made a 1 axis plasma cutting torch rail mechanism which is driven by an electric motor, this tool has a workspace/cutting length of 1300 mm, with tool sizes Length, width and height 1950 mm x 300mm x 100 mm. This mechanism/tool ​​can be installed on torches of several brands of plasma cutting, with various bracket speeds that can be adjusted as needed depending on the thickness of the plate being cut, from cutting speeds of 300 mm/minute to 2,000 mm/minute, adjustable cutting height 0 mm up to 10 mm, with a cutting angle setting of 0o to 90o and this mechanism tool can also be used portable / can be moved according to the required work location. Plasma cutting mechanism can be used to make it easier to make straight/horizontal cuts.